APPLICATION OF FEFLOW FOR THE SIMULATION OF GROUNDWATER FLOW AT THE TIRNAVOS (CENTRAL GREECE) ALLUVIAL BASIN AQUIFER SYSTEM - Koukidou, I.; Panagopoulos, A. (Bulletin of the Geological Society of Greece, 2010)
FEFLOW is a relatively new simulation code that was applied and tested systematically for the first time in Greece at Tirnavos alluvial basin, which is part of the eastern Thessaly plain. The aim of this exercise is to apply and test the applicability and versatility of FEFLOW in the simulation of groundwater flow of the Tirnavos basin aquifer system, which is located in eastern Thessaly-central Greece. From the compilation and calibration of the mathematical model, it can be concluded that FEFLOW is a very powerful tool with many practical applications and capabilities. Application of FEFLOW at Tirnavos basin was successful. As deduced by field data analysis, groundwater resources of the study area are overexploited, a fact which bears negative effects not only for the study area, but also for the surrounding area, which is much greater in extent. This fact was well reproduced in the simulation. It is therefore of utmost importance to rationally manage regional groundwater resources aiming at aquifer restoration (quantity and chemical quality) and the environmental protection of both the aquifer system and the depended and interrelated ecosystems, in accordance to the water related EC Directives.